(x平方+x)(x平方+x-2)=-1 用换元法
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 22:39:15
(x平方+x)(x平方+x-2)=-1用换元法(x平方+x)(x平方+x-2)=-1用换元法(x平方+x)(x平方+x-2)=-1用换元法设y=x²+x原方程即y(y-2)=-1y²
(x平方+x)(x平方+x-2)=-1 用换元法
(x平方+x)(x平方+x-2)=-1 用换元法
(x平方+x)(x平方+x-2)=-1 用换元法
设y=x²+x
原方程即 y(y-2)=-1
y²-2y+1=0
(y-1)²=0
y-1=0
y=1
x²+x-1=0
x=(-1±√5)/2
令x²+x=y,则原式化为y*(y-2)=-1,解得y=1 即x²+x=1,所以x=(-2+-根号下5)/2
(x平方+x)(x平方+x-2)=-1 用换元法
x/x平方-x+2=2x/x+1
方程2/X平方+X+3/X平方-X=4/X平方-1
2x平方-4x+1=2(x+?)平方+?
=(x平方+5x+4)(x平方+5x+6)+1 =(x平方+5x+4)平方+2(x平方+5x+4)+1
x平方-x+1=x平方-x分之6
7/x平方+x+1/x平方-x=0
x平方-3[2x-5(x平方-x+1)]
{x平方+x+1}{x平方+x+2}减12
2/x-x的平方-1/x的平方-x
9x平方=(X-1)平方
(2x+1)平方-x平方
x平方=2x
(x+1)平方-2x
x平方+x+1
(2x平方-3x+1)平方=22x平方-33x +1解方程
已知2x平方-7x+2=0,求x平方+1/x平方
X平方+3x+1=0 求:2x平方+X平方 分之 2